2017
DOI: 10.1111/add.13729
|View full text |Cite
|
Sign up to set email alerts
|

The costs of crime during and after publicly funded treatment for opioid use disorders: a population‐level study for the state of California

Abstract: Background and aims Treatment for opioid use disorders (OUD) reduces the risk of mortality and infectious disease transmission; however, opportunities to quantify the potential economic benefits of associated decreases in drug-related crime are scarce. This paper aimed to estimate the costs of crime during and after periods of engagement in publicly-funded treatment for OUD to compare total costs of crime over a hypothetical 6-month period following initiation of opioid agonist treatment (OAT) versus detoxific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…Our finding of positive and significant associations between monthly crime costs and drug use for the majority of stimulant use categories was consistent with other studies (Bennett et al, 2008; Oser et al, 2011), and similar in magnitude to crime cost estimates of drug users in-relapse or out-of-treatment, compared to in-treatment or abstinent (Flynn et al, 1999; Krebs et al, 2014; Krebs et al, 2016). Our finding that monthly crime costs associated with powdered cocaine use were not significantly different than crack cocaine was consistent with Vaughn et al (2010), who found no differences in violent behavior after controlling for contextual variables and co-morbid disorders.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding of positive and significant associations between monthly crime costs and drug use for the majority of stimulant use categories was consistent with other studies (Bennett et al, 2008; Oser et al, 2011), and similar in magnitude to crime cost estimates of drug users in-relapse or out-of-treatment, compared to in-treatment or abstinent (Flynn et al, 1999; Krebs et al, 2014; Krebs et al, 2016). Our finding that monthly crime costs associated with powdered cocaine use were not significantly different than crack cocaine was consistent with Vaughn et al (2010), who found no differences in violent behavior after controlling for contextual variables and co-morbid disorders.…”
Section: Discussionsupporting
confidence: 91%
“…The treatment variables included in our analysis represented an exploratory assessment of the potential for positive effects for stimulant users from non-stimulant-specific treatments, however, we would expect an effective, evidence-based treatment regimen for stimulant use disorders to have considerably larger effects. For example, if an effective treatment regimen was identified and capable of generating an 80% reduction in crime costs, similar to what has been recently estimated for OAT and opioid users (Krebs et al, 2014; Krebs et al, 2016), as well as individuals in long-term residential treatment for cocaine use disorders (Flynn et al, 1999), there are potential average monthly cost savings of $4691 per cocaine user, $4676 per daily MA user, and $7114 per daily polystimulant user treated. This is in addition to many other potential health benefits and cost savings, such as reduced health care costs, that could be generated by an effective treatment program (Baser et al, 2011; French and Martin, 1996).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The study demonstrated net savings from reduced health problems, illegal activity, and missed school days as a result of the criminal justice intervention. Krebs et al (2017) found significant cost reductions from implementing an opioid medication assisted therapy program in California. Researchers found that enrolling a client in the opioid assisted therapy program reduced the daily costs of crime during treatment compared with after treatment by $126 and that enrolling an individual in opioid assisted treatment (161 days) rather than traditional detoxification (19 days) reduced costs by $17,550.…”
Section: Discussionmentioning
confidence: 99%
“…Vital statistics data was obtained from the NDI, maintained by the Centers for Disease Control and Prevention (CDC), which contains records of all deaths occurring nationwide and probabilistic data linkage was performed by CDC staff 44 Mortality outcomes, treatment utilization and outcomes as well as the costs of crime associated with treatment engagement within the specified cohort have been described elsewhere and include further data collection details. 5,20,45,46 …”
Section: Methodsmentioning
confidence: 99%